ANALISIS PENGENAAN PAJAK PADA PELAKU E-COMMERCE - Ginting, Dea Cindi Amelia; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Transpublika Publisher, 2023)
In Indonesia, the use of information technology in business is growing rapidly. One of the impacts of technological advances is e-commerce. E-commerce allows customers to buy at smart brokers more conveniently. However, the rise of e-commerce raises concerns about how e-commerce businesses should be taxed. The tax base of e-commerce businesses is examined in this study. This study aims to analyze the analysis of tax imposition on e-commerce actors. The research method used in this study is the normative legal research method. The legal analysis is based on Regulation of the Minister of Finance of the Republic of Indonesia Number 210/PMK.010/2018 concerning Market Platform Providers and VAT NPWP. Legal basis for taxing online retailers. As a result, the implementation of tax collection on e-Commerce actors has not been efficient. According to Regulation Number 210/PMK issued by the Minister of Finance of the Republic of Indonesia. PMK 010/2018 Obligation to pay income tax in excess of non-taxable income in connection with tax procedures or procedures for carrying out online transactions through electronic systems. However, there are still many taxpayers who do not pay or avoid income tax. This problem is caused by non-compliance and lack of understanding of tax law in Indonesia.